2017
DOI: 10.3390/molecules22091453
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tannin Composition of Syrah Grape Skins and Seeds during Fruit Ripening under Contrasting Water Conditions

Abstract: Tannin accumulation and composition were determined in skins and seeds isolated from Vitis vinifera cv. Syrah grapes submitted to contrasting water regimes under semiarid climatic conditions. Three irrigation treatments were conducted, starting at berry set through harvest of two growing seasons, 2011 and 2012: irrigation at 100% of crop evapotranspiration ETc (FI), irrigation at 50% of ETc (DI) and non-irrigated (NI). Seed total tannins did not vary with maturity but those of skins underwent a progressive dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 49 publications
(125 reference statements)
12
35
0
Order By: Relevance
“…Bordiga et al , studying tannins during the maturation of Cabernet Sauvignon skins, found 1.2% galloylation at harvest. Kyraleou et al , evaluating the skins of the Syrah variety during maturation, found that the percentage of galloylation ranged from 4.23% to 9.51% in the oligomeric fraction and from 0.13% to 0.42% in the polymeric fraction.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bordiga et al , studying tannins during the maturation of Cabernet Sauvignon skins, found 1.2% galloylation at harvest. Kyraleou et al , evaluating the skins of the Syrah variety during maturation, found that the percentage of galloylation ranged from 4.23% to 9.51% in the oligomeric fraction and from 0.13% to 0.42% in the polymeric fraction.…”
Section: Resultsmentioning
confidence: 99%
“…The high concentrations of these compounds in the skin of Syrah grapes (IAC 313) may be related to the greater vigor of this rootstock compared to that of 1103P in the tropical climate condition of the study, which provides greater coverage of the canopy and protection of the grape clusters from the solar radiation and high temperatures. According to some studies, shading reduces the relative content of procyanidins in grapes grown under traditional conditions …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations